Tecnologia e concepção de sistemas estruturais híbridos de concreto para edifícios de múltiplos pavimentos no Brasil - Takata, Leandro Teixeira (Universidade Federal de São Carlos, 2017)
Considered as a modern method of construction (Modern Methods of Construction, or simply MMC), the hybrid construction system presents several advantages over other systems. It combines the benefits of precast construction with the advantages of cast in place with lower costs and higher quality of the elements, in addition to offer competitive (compared to more traditional) structures with good quality and durability. There is a great tendency in construction in trying to use characteristics of different constructive systems that can bring benefits in buildings. In hybrid construction systems, the idea is to use advantages of more than one system with different characteristics. In this work, the proposal is to look for systems, in principle, with characteristics of precast and cast in place, to use them in the same building. Some advantages and disadvantages of this system are presented, as well as the national and international scenario of their application. It is attempted to show from the current condition of civil construction, as it is already possible to apply the union of the two systems: the precast and cast in place concrete for making of vertical constructions. The idea of the work is to present a study of how structures with hybrid construction system can be applied in buildings. The interactions of the chosen systems are studied, how they can be executed in the face of different needs and conditions, and what costs entail the beginning and end of the work. Some examples of calculation are presented to illustrate the differences and similarities with cast in place and precast. An example of the cost between the constructive systems is also presented, so that they can serve as base for an additional option in the definition and choice of the constructive system.
Keywords: Sistema construtivo híbrido; Moldado no local; Pré-fabricados; Viabilidade estrutural e financeira; Hybrid construction system; Cast in place; Precast; Structural and financial feasibility; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS